Global burden of cardiovascular diseases attributed to low physical activity: An analysis of 204 countries and territories between 1990 and 2019 - Yanfang Luo; Jinguang Liu; Jinshan Zeng; Hailin Pan (Elsevier, 2024)
Background: Low physical activity is a major risk factor for cardiovascular diseases (CVDs). This study aimed to estimate the global, regional, national, and sex-age-specific burden of CVDs attributed to low physical activity from 1990 to 2019. Methods: We leveraged data from the Global Burden of Disease Study 2019 to compute the number of fatalities, disability-adjusted life years (DALYs), age-adjusted mortality rates (ASMR), and age-adjusted DALY rates (ASDR) attributed to CVDs resulting from low physical activity. Furthermore, we scrutinized the trends and correlations of these metrics in connection with the socio-demographic index (SDI) across 21 regions and 204 countries and territories. Results: The global deaths and DALYs due to CVDs caused by low physical activity increased from 371,042.96 [95 % UI: 147,621.82-740,490] and 6,282,524.95 [95 % UI: 2,334,970.61-13,255,090.08] in 1990 to 639,174.92 [95 % UI: 272,011.34-1,216,528.4] and 9,996,080.17 [95 % UI: 4,130,111.16-20,323,339.89] in 2019, respectively. The corresponding ASMR and ASDR decreased from 12.55 [95 % UI: 5.12-24.23] and 181.64 [95 % UI: 71.59-374.01] in 1990 to 8.6 [95 % UI: 3.68-16.28] and 127.52 [95 % UI: 53.07-256.55] in 2019, respectively. Deaths and DALYs attributed to low physical activity were initially higher in males but shifted to females after 70-74 age group. Both genders had increasing death rates, peaking at 80-84 age group. Most CVDs deaths and DALYs number are caused by ischemic heart disease. The highest burden of CVDs attributed to low physical activity was observed in North Africa and the Middle East. The lowest burden was observed in Oceania and High-income Asia Pacific. There was a distinctive 'n-shape' relationship between the regional SDI and the ASDR of CVDs attributed to low physical activity from 1990 to 2019. Conclusion: The global impact of CVDs stemming from low physical activity remains substantial and demonstrates substantial regional disparities. As individuals age, this burden becomes more prominent, particularly among females. Efficacious interventions are imperative to promote physical activity and mitigate the risk of CVDs across diverse populations and regions.